2000
DOI: 10.1054/bjoc.1999.0935
|View full text |Cite
|
Sign up to set email alerts
|

Detection of codon 12 K- ras mutations in non-neoplastic mucosa from bronchial carina in patients with lung adenocarcinomas

Abstract: K- ras activation by point mutation in codon 12 has been reported in lung adenocarcinomas in various models of experimental lung tumours induced by chemical carcinogens. The hypothesis of the presence of cells containing K- ras mutation in non neoplastic bronchial carina, the main site of impaction of airborne contaminants, was investigated by evaluating concurrent lung tumour and non-neoplastic proximal bronchial carinae from 19 patients with lung adenocarcinomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…25 The same transition has been described in preneoplastic lesions, such as aberrant crypt foci (ACF) in the colon, 26 or even phenotypically normal mucosa located near neoplastic lesions, as in the case of nonneoplastic mucosa from bronchial carina in patients with lung adenocarcinomas. 27 In the present study, mutations were not observed in control tissues, including peripheral blood and phenotypically normal conjunctival specimens, harvested from the same patients, implying that the mutations detected may be specific for pterygium.…”
Section: Discussioncontrasting
confidence: 43%
“…25 The same transition has been described in preneoplastic lesions, such as aberrant crypt foci (ACF) in the colon, 26 or even phenotypically normal mucosa located near neoplastic lesions, as in the case of nonneoplastic mucosa from bronchial carina in patients with lung adenocarcinomas. 27 In the present study, mutations were not observed in control tissues, including peripheral blood and phenotypically normal conjunctival specimens, harvested from the same patients, implying that the mutations detected may be specific for pterygium.…”
Section: Discussioncontrasting
confidence: 43%
“…In another study, Clements et al (1995) analysed bronchoscopy specimens obtained from lung cancer patients and showed that K-ras mutations were found in both malignant and nonmalignant tissues in 22.7% (5 of 22) of the patients and in only nonmalignant tissue in 9.1% (2 of 22) of the patients. Finally, a recent study by Urban et al (2000) showed that K-ras mutations were detected in both lung tumour and bronchial carina tissue in 21% (4 of 19) of the patients, while being present only in the bronchial carina but not in the tumour in 11% (2 of 19) of the patients. These latter studies and our present study showed that K-ras mutations can be frequently found in non-neoplastic lung tissues, including histologically normal tissues.…”
Section: Figurementioning
confidence: 93%
“…Although K-ras mutations have been frequently found in lung tumours, the timing of their occurrence in the multistep process of lung carcinogenesis remains poorly understood. Such studies used tissue specimens removed at biopsy or resection (Sugio et al, 1992;Westra et al, 1993;Clements et al, 1995;Yakubovskaya et al, 1995;Urban et al, 1996;Keohavong et al, 1997b;Urban et al, 2000), and cell samples microdissected from embedded lung tissue sections (Sugio et al, 1994;Westra et al, 1996). Taken Topographic analysis of K-ras mutations in histologically normal lung tissues and tumours of lung cancer patients together, some of these studies suggest that K-ras mutations occur relatively late in lung cancer development (Sugio et al, 1994;Yakubovskaya et al, 1995;Urban et al, 1996), while other studies indicate that they could represent early events in this process (Li et al, 1994;Clements et al, 1995;Keohavong et al, 1997b;Urban et al, 2000).…”
mentioning
confidence: 99%
“…This may in turn explain the frequent simultaneous occurrence of KRAS mutations and alterations of the p16INK4A/p14ARF and/or p53 pathway in cancer cells, and suggests the occurrence of RAS mutations in an ordered multi-step manner during the carcinogenic process. Although there has been considerable controversy over whether KRAS mutations are present in pre-malignant or normalappearing lung tissues (Sugio et al, 1994;Urban et al, 2000), KRAS mutations are reportedly present in 25 -40% of AAH lesions (Westra et al, 1996;Cooper et al, 1997). Among the RAS family members, the KRAS gene is most frequently affected in lung cancers, usually at codon 12 Mills et al, 1995), while mutations of HRAS or NRAS are very rare (*1%) in lung cancers.…”
Section: The Ras Gene Familymentioning
confidence: 99%